Two effects of combined nitrogen on the adhesion of Rhizobium etli to bean roots - Pérez Giménez, Julieta (2013)
Combined forms of nitrogen negatively influence rhizobia-legume symbiosis. The effects of combined nitrogen are known for nodulation and dinitrogen (N2) fixation, but little is known about the effect on preinfection events. Here, we studied the effects of combined nitrogen on the adhesion of Rhizobium etli to common bean (Phaseolus vulgaris L.) roots. When potassium nitrate (KNO3) or sodium glutamate was added to an incubation mixture of rhizobia and plants that were previously grown in nitrogen-free solution, rhizobial adhesion to roots was stimulated. However, the rhizobial adhesion to bean roots that were previously grown with 10 mM KNO3 was reduced by half. A fraction of the bean root exudates, which is thermolabile and has molecular mass larger than 12 kDa stimulated rhizobial adhesion, but this stimulatory activity was lost in root exudates obtained with 10 mM KNO3. Thus, the inhibition of symbiosis in response to combined nitrogen may be controlled by the plant at the preinfection stage as well.